13 Paediatric cardiac CT – current state of play and room for improvement. (18th May 2017) - Semple, Thomas; Minden, Tom; Gartland, Nathalie; Castellano, Isabel; Holubinka, Michael; Rubens, Michael; Padley, Simon; Owens, Catherine M; Nicol, Edward
Abstract : Introduction: Despite significant technologic advancements, application of cardiac CT techniques to paediatric imaging continues to push technology to its limit. We examined indications for paediatric cardiac CT and the impact of advances in technology on dose and use of ECG-gating techniques between 1st, 2nd and 3rd generation dual-source scanners. Methods: Retrospective collection of indications from a radiology information system. Comparison of cardiac, high-pitch ?spiral acquisitions during 6-month periods in 2014 (Definition DS), 2015 (Flash) and 2016 (Force) across 2 institutions. Whole-study DLP (32 cm phantom) used for simple comparison of dose. Proportion of scans performed as spiral, prospective and retrospective ECG-gated compared across generations of scanner. Results: The majority of CTs were for complex congenital heart disease assessment (shunts, pulmonary vessels and aortic anatomy including major aortopulmonary collateral arteries). In the 6-months' examined, 12 protocols were used on the definition DS, 17 on the Flash and 4 on the Force. 14.3% of cardiac scans were acquired with retrospective and 20% with prospective ECG-gating on the 1st generation machine with all examinations performed as high pitch spiral acquisitions on the 3rd generation machine. Moving from a 1st to a 3rd generation dual source scanner resulted in 72, 72 and 73% decreases in DLP in 0–2, 2–5 and 5–10 year-olds respectively. Conclusions: CT is capable of non-invasive complex anatomic assessment in neonates and children. As technology advances, application of cardiac CT in this hard to image population becomes simpler with fewer protocols, less need for multiphase acquisitions and lower ionising radiation doses.